Senergisitas perkembangan Kognitif dengan Perkembangan Afektif pada Mata pelajaran Matematika SDN 26 Dompu. - Astiati, Siska Dwi; Ilham, Ilham; Aidin, Aidin (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2022)
The concept of cognitive and effective learning requires the existence of main principles such as active learning, meaning that students as learning subjects are the most important factor, students learn to actively learn independently. This study aims to (1) determine cognitive development in the subjects of SDN 26 Dompu, (2) determine affective development in Mathematics subjects at SDN 26 Dompu, (3) determine cognitive development with affective development in Mathematics subjects at SDN 26 Dompu. The method of collecting data obtained from the results of the instrument and documentation as a complement. The data analysis technique used descriptive statistical analysis. From the results of data analysis, the lowest cognitive score in mathematics was 60 so it was grouped into "medium", after being averaged it was 63.93 so it was grouped into "high", and for the highest cognitive score in mathematics was 83, so it was grouped " high", after being averaged is 75.52 categorized as "high". From the results of the analysis, the value of tcount = 0.68 while ttable at a significant level of 5% and 1%, respectively, is 0.297 and 0.361. Because tcount < ttable means in this case it can be said that H0 is rejected. From the results of this study, it can be concluded that the accepted hypothesis in this study is that there is a match between cognitive development and affective development in mathematics subjects at SDN 26 Dompu.